Efficacy of human resources management practices on the performance of small and medium scale enterprises - Kowo Solomon Akpoviroro; Odumesi Abolaji Oladimej; Igwe Nnenwogo (Економіка та управління АПК, 2025)
Human Resources Management Practices (HRM) is recognized as being essential to the success of Small and Medium Scale Enterprises (SMEs). The objectives of this research was to examine the effect of human resource management practices on SMEs growth in Ogun State and also to determine the adoption of human resource management practices on performance of SMEs. The primary data was gathered using structured questionnaire. The survey method was used and a cross-sectional design was adopted. Selected SMEs in the two local government area of Abeokuta (Abeokuta South LGA), and (Abeokuta North LGA) were object of the study. The data was analyzed using statistical package for the social sciences, (SPSS). It also made use of analysis of variance (ANOVA), Simple linear regression analysis was used to test hypotheses one and correlation analysis was employed to test hypothesis two. The study indicatesthat Human resources management practices is a significant predictor of SMEs in Ogun state and there is a significant effect between Adoption of HRM practices and SMEs performance in Abeokuta, Ogun state. The study recommended that Organization need to have an effective recruitment policy to promote scientific selection of prospective employees. The departments should participate in selection process as they have different preferences in the candidates. Candidates need to be selected based on requisite skills knowledge, attitude and qualification using appropriate selection techniques